Integrated Green Chemistry Problem-Based Learning Module Development to Improve Science Process Skills Senior High School Students on Basic Chemicals Law - Rahmi Eka Witri; Hardeli; Desy Kurniawati; Yerimadesi (Jurnal Penelitian Pendidikan IPA, 2023)
The implementation of the independent curriculum at the senior high school level can be an opportunity for educators to develop alternative teaching materials that according to the latest curriculum standards. One alternative teaching material that can be used is the module. This study aims to develop a basic chemical law module based on Problem Based Learning integrated with green chemistry that is valid, practical and effective. This type of research is educational development research (educational design research) or known as EDR. The test subjects for this study were three chemistry lecturers, two chemistry teachers, and tenth grade students. The results of the study obtained a construct validity of 0.90 and a content validity of 0.91. The results of practicality tests by teachers and students are included in the very practical group with respective values of 0.88 and 0.84. The results of the t test on student learning outcomes showed that t-count (2.87) is bigger than t-table (1.67), and the value of science process skills in the experimental class was higher than the control class. Therefore, it can be said that the module based on problem base learning integrated with green chemistry on basic chemical law material is valid, practicable, and effective. Therefore, it can be said that the modules made are reliable and useful for use in the learning process.